Development of fluorescent FRET probe for determination of glucose based on β-cyclodextrin modified ZnS-quantum dots and natural pigment 3-hydroxyflavone. (May 2016) - Dong, Ling-Yu; Wang, Li-Yun; Wang, Xiang-Fang; Liu, Yuan; Liu, Hai-Ling; Xie, Meng-Xia
Abstract: An environmental friendly fluorescence resonance energy transfer probe for determination of glucose has been developed. The natural pigment, 3-hydroxyflavone, can enter the hydrophobic cavity of beta-cyclodextrin functionalized ZnS quantum dots, forming a fluorescence resonance energy transfer system with beta-cyclodextrin modified ZnS quantum dots as energy donor and 3-hydroxyflavone as energy acceptors. Glucose can be oxidized with assistance of the glucose oxidase to quantitatively produce hydrogen peroxide, which could rapidly quench the fluorescence intensity of the 3-hydroxyflavone in the probe by catalysis of horseradish peroxidase. The probe was successfully applied to determination of glucose in human serum and urine samples, and the results indicated that the average spiking recoveries of glucose ranged from 102 to 113%, with relative standard deviations below 15%. The developed approach were simple and possessed high sensitivity and selective for glucose, and this work provides a new clue for developing fluorescent probe. Highlights: Environmental friendly fluorescent FRET probe for detection of glucose was developed. Natural pigment 3-hydroxyflavone can form FRET system with β-CD-modified ZnS QDs. Hydrogen peroxide can oxidize 3-HF and lead to fluorescence quenching of the probe. The probe was applied to determination of glucose in human serum and urine samples. Developed approach was simple and with high sensitivity and selective for glucose.